PEMBERDAYAAN MASYARAKAT PERUMAHAN DALAM UPAYA MENINGKATKAN PENGETAHUAN KEAGAMAAN - Uli Wildan Nuryanto; Ahmad Munawir; Basrowi Basrowi (Gapenas Publisher, 2023)
The religious culture of the housing community is enthusiastic about the existence of religious learning, especially among gentlemen where in today's scope with the dominance of the multicultural culture of the housing community from various ethnic, customary, cultural and educational backgrounds in the Talaga Bestari housing complex rw 05 rt 08 Wanakarta Village Sindang Jaya District, Tangerang Regency has great potential as an effort to increase religious knowledge in the area. However, due to limited knowledge about environmental religion, there is still a lack of religious knowledge in this area. The purpose of community service research is to provide an understanding of the community regarding the development of religious potential and provide weekly recitation forms as a form of community understanding of the potential for religion in the Talaga Bestari Housing Complex. Sindang Jaya District, Tangerang Regency. The teaching method used is weekly recitation and practice for community groups which will later provide education to families and other communities about the religion of fiqh science. Data collection techniques through pre-test and post-test. The results of community service regarding religious studies